Farming - a way-of-life to be proud of? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Young people who decide to pursue a career in farming face many pressures. They may struggle to obtain farm inputs or credit. They may also feel ashamed because they are not working in a ?respectable? white-collar job. This report from Zambia features two young people who describe how they have overcome these difficulties.